Theoretical and Methodological Basis of Assessment of Reading Comprehension in Mother Tongue Education - Shohruh Abdiraimov (Periodica Journal, 2023)
This article examines the process of assessing students' knowledge, skills and abilities from a pedagogical and methodological point of view, analyzes the psychophysiological and psycholinguistic bases of assessing students' reading comprehension in their native language, and analyzes the current state of assessment of students' reading comprehension in general secondary education. Theoretical and methodological views on the content, criteria and methods of assessment of students' ability to read and understand texts in their native language are also presented. These scientific and methodological recommendations have been tested. The results of the experiments were analyzed on the basis of mathematical and statistical methods, and scientific conclusions were made on improving the theoretical and methodological basis for assessing students' ability to read and understand texts in their native language.
Keywords: assessment; reading comprehension; psycholinguistics; psychophysiology